2021
DOI: 10.1136/annrheumdis-2021-eular.3031
|View full text |Cite
|
Sign up to set email alerts
|

Ab0292 a Retrospective Study of Perioperative Management of Patients With Sle in Total Hip Arthroplasty

Abstract: Background:Aseptic necrosis (AN) of bones is one of the most serious complications of systemic lupus erythematosus (SLE), which is characterized by multicomponent joint damage mainly in young people. Long-term observations show that two thirds of patients have multiple aseptic necrosis of bones, with the femoral head being most often affected. Obviously, caused by much strain on the hip joint. In this regard, total hip arthroplasty (THA) is an integral part of the treatment of SLE patients. Despite the fact th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In patients with SLE, disease activity and infection are the two leading causes of postoperative death [ 3 ]. Some studies have reported several complications of total hip replacement in patients with SLE and postoperative Harris hip scores (HHS) and other functional scoring results [ 7 16 ]. At present, there is no clear consensus on the impact of complications after THA in patients with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with SLE, disease activity and infection are the two leading causes of postoperative death [ 3 ]. Some studies have reported several complications of total hip replacement in patients with SLE and postoperative Harris hip scores (HHS) and other functional scoring results [ 7 16 ]. At present, there is no clear consensus on the impact of complications after THA in patients with SLE.…”
Section: Introductionmentioning
confidence: 99%